Internet use and depressive symptoms among Chinese older adults: Two sides of internet use - Aruhan Mu; Shanshan Yuan; Zhiyong Liu (Frontiers Media S.A., 2023)
ObjectiveTo explore the relationship between internet use which includes time spent on the internet, internet skills, types of online activities, and depressive symptoms in older adults.MethodsWe used 2020 China Family Panel Studies (CFPS) data with 3,171 older adults aged 60 years. Depression symptoms were measured with the Center for Epidemiologic Studies Depression (CES-D), and internet use was measured by time spent on the internet, internet skills, and types of online activities. Multiple linear regression models were used to explore the relationship between internet use and depressive symptoms in older adults.ResultsLonger time spent on the internet was associated with higher scores of depressive symptoms (β = 0.14). Higher internet skills were associated with lower scores of depressive symptoms (β = −0.42). Watching short-form videos (β = 1.34) was associated with higher depressive symptom scores, and the use of the WeChat function (β = −0.96) was associated with lower depressive symptom scores, while online games and online shopping were not significant.ConclusionThe effect of internet use on depressive symptoms in older adults is a double-edged sword. Controlling the time spent on the internet, improving internet skills, and guiding specific a type of online activities in older adults can improve depressive symptoms through rational use.